Fostering Diversity in Congregations: A practical framework for local churches to reflect and improve accessibility - Kauhaus, Hanna (Ecclesial Futures, 2025)
Diversity, understood as the extent to which the members of a group or organization differ from one another, is fundamental for the Church, but often not given to a great extent in local congregations, at least not in the Evangelical Church in Germany. This article wants to support practitioners in a diversity-oriented development process for their local churches. In the first part, the concept of diversity management is introduced and some ideas pointed out and adapted for congregational development. Taking these basic ideas and additionally systematizing some suggestions from tools for diversity-oriented organizational development, in the second part a practical framework is presented. It has been created for identifying barriers and finding starting points for enhancing diversity in local protestant churches in Germany. Based on a model of four levels of accessibility and exclusion, the core is a framework of five areas of church activities in which unconscious barriers can be found regarding these different levels of accessibility. The aim is to help congregations to take some manageable steps to better include all who are already present and to become more accessible for others who are different in certain dimensions of diversity.